Conservation in the internet age: threats and opportunities - Levitt, James N. Ed. (Washington : Island Press, 2002)
Computer Science
Keywords: Nature conservation; Internet; Networks; The potential impact of new networks; Internet use in a high growth; Internet age as context for conservation innovation